Cardiac contraction-induced GLUT4 translocation requires dual signaling input. (August 2015) - Luiken, Joost J.F.P.; Glatz, Jan F.C.; Neumann, Dietbert
Highlights AMPK and PKD1 are each required for contraction-stimulated glucose import. Simultaneous activation of two signaling pathways creates a dual signaling input. The necessity for dual signaling input refines subsequent metabolic responses.